On the Measurement of Subjective Apprehension Risk - Roche, Sean Patrick (Criminal justice review, 2022)
Do people think about offending risk in verbal or numerical terms? Does the elicitation method affect reported subjective probabilities? Rational choice models require potential outcomes (e.g., benefits/costs) to be weighted by their probability of occurrence. Indeed, the subjective likelihood of being apprehended is the central construct in criminological deterrence theory—the so-called certainty principle. Yet, extant literature has measured the construct inconsistently and with little attention to potential consequences. Using a series of randomized experiments conducted with nationwide samples of American adults (aged 18 and over), this study examines the degree of correspondence between verbal and numeric measures of apprehension risk, assesses the durability of numeric estimates specifically, and attempts to elicit how respondents naturally think about apprehension risk. The findings suggest that laypeople are somewhat inconsistent in their use of both verbal and numeric descriptors of probability, their numeric estimates of probability are unlikely to be precise or durable, and many seem to prefer thinking of risk in verbal terms (compared to numeric terms). Researchers should consider including both verbal and numeric measures of probability and explore alternative measurement strategies, including anchoring vignettes, which have been valuable in standardizing verbal responses in other disciplines.